2017
DOI: 10.1111/jdi.12710
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of carotid atherosclerosis in elderly patients with type 2 diabetes at different disease course, and the intervention by statins in very elderly patients

Abstract: IntroductionChronic complications of diabetes have become the leading cause of death in elderly patients with diabetes. Carotid atherosclerosis, one of the major complications, was evaluated and the effects of atorvastatin on carotid atherosclerosis in very elderly patients with type 2 diabetes were observed.Materials and MethodsPatients were divided into three groups: (i) disease course <5 years; (ii) disease course 5–10 years; (iii) disease course >10 years, and carotid atherosclerosis was evaluated. The ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Furthermore, they may become increasingly worried about the severity of DE and the effect of treatment, which may then lead to depression and anxiety. This finding was consistent with previous studies on other diseases, which show that long disease duration, severe symptoms, and impaired social function were associated with anxiety and depression (73).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, they may become increasingly worried about the severity of DE and the effect of treatment, which may then lead to depression and anxiety. This finding was consistent with previous studies on other diseases, which show that long disease duration, severe symptoms, and impaired social function were associated with anxiety and depression (73).…”
Section: Discussionsupporting
confidence: 93%
“…Continuous exposure to hyperglycemia, oxidative stress and increased systemic inflammation factors might induce many changes in the vascular that might accelerate atherosclerosis 18,19 . Compared with the healthy control group, the carotid intima-media thickness values of diabetes patients were significantly higher 20 . Diabetes patients showed a greater percent atheroma volume and total atheroma volume in coronary atherosclerosis 19 .…”
Section: Discussionmentioning
confidence: 71%
“…Surprisingly, the duration of type 2 diabetes mellitus was not significantly associated with intracranial plaque enhancement or plaque burden. Compared with patients who had type 2 diabetes mellitus for <5 years, carotid plaque vulnerability and the intima-media thickness values of patients with type 2 diabetes mellitus for >10 years were obviously higher 20 . A retrospective study showed that the prevalence of peripheral arterial and coronary atherosclerosis significantly increased with the duration of type 2 diabetes mellitus 27 .…”
Section: Discussionmentioning
confidence: 78%
“…Virtual-histology intravascular ultrasound (VH-IVUS) can evaluate plaque stability in vivo. According to the VH-IVUS classification, thin fibrous cap atherosclerosis is closely related to future cardiovascular events and is known as vulnerable plaques [ 2 ]. Changes in serum adipokine C1q/tumor necrosis factor-related protein 9 (CTRP9), amyloid A (SAA), and plasma homocysteine (Hcy) levels can be used as indicators to reflect the stability of coronary atherosclerotic plaque [ 3 ].…”
Section: Introductionmentioning
confidence: 99%